IMPORTANCE OF SOME NATURAL RELATIONS PLANTS - ARTHROPODS IN AGRICULTURE IN THE WARM ZONE OF CENTRAL TOLIMA - HALLMAN, GUY (Revista Colombiana de Entomología, 1979)
Natural relations between the wild flora of an agroecosystem and arthropods can have an influence on the pest problems that occur in the crops. Pests that breed in wild plants can later infest crops, and parasites and predators of arthropods that infest the wild flora may also attack crop pests. This study was conducted from November of 1976 to May of 1979 to investigate the role of some natural plant-arthropod relationships existing in the warm region of central Tolima. The roles of over 40 plant feeders in 30 wild plants were determined. Several natural enemies of these plant feeders were also found. The most promising relationship for the agriculture of the region appears to be increasing natural populations of Trichogramma sp. (Hymenoptera: Trichogrammatidae) through the conservation of Turnera ulmifolia L. (Turneraceae). This plant is infested by a good host of Trichogramma, Euptoieta hegesia (Gr.) (Lepidoptera: Nymphalídae). The presence of aphids (Homoptera: Aphididae) in the wild flora will increase populations of some general predators which may then attack pests in crops. Agrius cingulatus (Fabr.) (Lepidoptera: Sphingidae) might offer biological control of the important weed, Ipomea triloba (Convolvulaceae).